Mining for a week or for centuries: Variable aims of flint extraction sites in the Mons Basin (Province of Hainaut, Belgium) within the lithic economy of the Neolithic (Journal of Lithic Studies, 2016)
The Mons Basin (Province of Hainaut, western Belgium) is a geologically rich region, particularly from the point of view of Upper Cretaceous sedimentary deposits, conducive to an important flint gathering activity during the whole regional Prehistory. Focusing on the Neolithic period, indications of flint procurement as early as the end of the 6th millennium have been recorded, but there are concrete evidences of mining sites in the region since the second half of the 5th millennium. Flint extraction activities have lasted at least until the second half of the 3rd millennium. According to literature and recent researches, eleven sites could be extraction sites, including the World Heritage site of Spiennes. This paper critically assesses the accuracy of the data available and focuses on the issue of the unequal function of these extraction sites and their socio-economic function for Neolithic communities. Is it really possible to establish a hierarchy between the extraction sites? Can different acquisition-production strategies be highlighted? These questions are dealt with by synthesizing the data concerning the methods of flint exploitation in the Mons Basin, the qualitative and quantitative characteristics of the products relative to the production intentions but also by addressing the issue of their importance in exchange networks.